Let's Go to the Mosque!. - Khan, Hasan. (Tufts University. Tisch Library., 2021)
This children's book was created for Tufts University course CSHD190 Children with Special Needs (Fall 2020, Professor Leandra Elion) Students created books for and about children with physical and/or intellectual disabilities.; Keywords: visible disability, Islam, religious community, prayer, audiobook, hand-drawn.; Excerpt from author's statement: "Let's Go to the Mosque!" aims to describe the kind of welcoming Muslim community I experienced while growing up. Mosques beyond just my own provide subtitles for khutbas and services, audiobooks, Qur'ans in braille, open floor plans, and more. Above all else, prayer is not understood as strict physical acts but a state of mind that everyone embodies personally.; A storyboard for the book is also available to download from this record.